Organic LEDs: Sky‐Blue Organic Light Emitting Diode with ≈37% External Quantum Efficiency Using Thermally Activated Delayed Fluorescence from Spiroacridine‐Triazine Hybrid (Adv. Mater. 32/2016). Issue 32 (August 2016) - Lin, Ting‐An; Chatterjee, Tanmay; Tsai, Wei‐Lung; Lee, Wei‐Kai; Wu, Meng‐Jung; Jiao, Min; Pan, Kuan‐Chung; Yi, Chih‐Lung; Chung, Chin‐Lung; Wong, Ken‐Tsung; Wu, Chung‐Chih
Abstract : Extremely efficient blue organic electroluminescence with external quantum efficiency of 37% with a conventional planar device structure is reported by K.‐T. Wong, C.‐C. Wu, and co‐workers on page 6976. Such a high efficiency is realized by thermally activated delayed fluorescence emitters based on spiroacridine–triazine hybrids, which simultaneously possess nearly 100% photoluminescence quantum yield and strongly horizontally oriented emitting dipoles.